388 Patient-Specific 3D Printed Talus Truss Cage with Hindfoot Nail Arthrodesis – a Novel Salvage Procedure for Complex Post-Traumatic Talus Avascular Necrosis. (19th August 2022) - Morris, Richard; Cheruvu, Manikandar Srinivas; Lingnau, Leonie; Mumtaz, Haroon
Abstract: Background: Post-traumatic avascular necrosis (AVN) following talus fracture can be a devastating injury, with subsequent destruction of the tibio-talar-calcaneal articulations resulting in joint degeneration and compromised mobility. Tibio-talar-calcaneal arthrodesis is a salvage procedure where large bone voids can present significant challenges. Whilst a range of arthrodesis techniques have been described, we present a unique case of patient specific 3D-printed talus truss cage with navicular articulation and hindfoot nail fusion. Case Presentation: We present a case of an 80-year-old fit and well gentleman who was a delayed presentation with a Hawkins 3 talar neck fracture and a Mueller AO / OTA C3 talar body fracture. The patient opted for a trial of conservative management over primary fusion, but at 3 months post-injury there was talar body collapse and progression of subtalar degeneration, therefore he underwent talus fixation with subtalar fusion. At 6 months post-injury, there was collapse of the tibio-talar joint with AVN of the talus. The patient had ongoing discomfort and a decision was made to proceed with custom implant arthrodesis. At 7 weeks post-operatively the patient's wounds have healed without complication and talus height is maintained. Follow-up is ongoing. Discussion: The mainstay of treatment for severe post-traumatic talar AVN has been arthrodesis of the hindfoot and ankle with complication rates as high as sixty percent, including mal-union and loss of bone height. This case highlights the potential of a patient specific 3D-printed talus truss cage to manage complex bone defects and these challenges of arthrodesis.